PENERAPAN PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN SISWA KELAS II SEKOLAH DASAR - Anyela Merici (Program Studi PGSD Universitas Flores, 2023)
In class II of the Merico room at Santa Ursula Ende Catholic Elementary School, students generally experience difficulties when asked to work on questions, both on the blackboard and in books, even though the students actually have good abilities. To overcome the problems above, the step that needs to be taken is to apply a problem based learning model. This research aims to improve Mathematics learning outcomes in class II fraction material by using a problem based learning model at Santa Ursula Catholic Elementary School in Ende, Ende Regency for the 2023/2024 academic year. This type of research is Classroom Action Research (PTK). This research went through the stages of planning, implementation, observation and reflection. The results of the descriptive analysis revealed that in cycle I the average student score was 69.88 and learning completeness reached 48%, while in cycle II the average student score was 82.22% and learning completeness reached 89%. In this way, the use of the problem based learning model can improve the mathematics learning outcomes of fraction material for Class II students in the Merico room at Santa Ursula Catholic Elementary School, Ende for the academic year 2023/2024.